EDUCATION FOR WORK RELATED TO LIFESTYLE HEALTH - Dinu, Marinel Cornelius; Goga, Nicolae; Neagu, ANA MARIA; Ancuceanu, Robert (Annals of Spiru Haret University. Economic Series, 2020)
Studies performed in various countries, including Romania, have shown that a number of factors are negatively impacting the health of the population at the workplace and in the household. The connection between health and work has been researched for a number of years as an important driver towards wellbeing. Several studies have been conducted in order to identify problems and to find solutions to harmonize the balance between wealth and health. Increased globalization, the chase for competitive advantage and the reduction of costs (especially labor costs) moved employee attention of from the wellbeing of employees to higher profits. We discuss about such situations mainly in the East European Countries since the labor force is cheaper than in Western Europe. We should not forget that this current trend started in the US and was adopted also by European companies in order to increase profits. In West Europe there are quite a number of studies regarding relation between work and health, while in East Europe the number of such studies is quite small. The present paper proposes as an objective the study of several working factors and the relationship to health in Romania. Some of the results in our study reveal the concordance between the propensity of individuals to sacrifice from their one time and time for work without significant discrepancies between genders. Also the more people invest in their time to rest, the more they are able to work hard without injuries. When it comes to gender characteristics we determined slight changes in behavior with almost the same labor pattern for both participants. Another interesting finding was that rural and urban areas are clearly determining the type of stress exposure for participants with a higher impact for workers coming from the urban area. Physical exercise and labor can be channeled in good order according to the gender capabilities.